538 Using general population job-exposure matrixes to estimate workplace biomechanical exposures: new opportunities and international comparisons. (24th April 2018) - Evanoff, BA; Descatha, A; Buckner-Petty, S; Dale, AM; Andersen, J
Abstract : Introduction: Job Exposure Matrixes (JEMs) are commonly used in epidemiological studies of chemical and physical hazards; recent work has used JEMs to estimate workplace biomechanical exposures in studies of musculoskeletal disorders (MSDs). We conducted cross-national comparisons of general population JEMs from Denmark, France, and the USA. Prior studies using the Danish and US JEMs showed associations between MSD and workplace exposures to force, repetition, and posture. Methods: JEMs were constructed in the three countries using different methods to estimate workplace biomechanical exposures: Denmark (expert assessment), France (pooling of self-reported exposures from >28 000 current workers), and the USA (combined methods using O*NET, a national job demands database). Each JEM assigned multiple exposures to workers at the level of the job code. We created cross-walks between the respective national coding schemes (DISCO, PCS, and SOC) to compare estimated exposures at the level of the job. Results: Comparison between the Danish and US JEMs showed fair to moderate agreement for 7 lower extremity exposures across 168 job codes (kappa 0.25 to 0.56 across 7 exposures), and moderate to substantial agreement for 10 shoulder exposures across 336 jobs (kappa 0.38 to 0.77). Similar agreement was found when comparing 8 exposures between the French and American JEMs across 335 job codes. We will report additional analyses now in progress, including the strength of association between MSDs and exposures estimated by different JEMs when applied to the same datasets. Discussion: JEM for biomechanical exposures are a useful and efficient means to estimate workplace biomechanical exposures, particularly in large general population studies where exposure data are otherwise limited. Cross-national comparison studies are a useful methodological step as the use of JEM for studies of MSD continues to increase. Ongoing validation studies will increase the usability of JEMs in providing exposure-response estimates and further guidance for prevention of MSDs.